Nutritional improvement and physicochemical evaluation of liver pâté formulations - Terrasa, A. M. (2016)
Pâté formulations composed of chicken liver, a by-product of poultry industry, have been produced by replacing pork back fat with sunflower oil and reducing fat content. The characterization of these products was performed, while the oxidative stability, microstructure, texture, colour, and hygienic quality were determined throughout refrigerated storage. The hardness of pâtés with sunflower oil was lower than the other ones. Different microstructures regarding protein matrix, fat globules and pores, were associated with fat type and content. The storage time, fat type and content influenced the colour parameters. In terms of the oxidative stability, no reduction in the product quality was found during the refrigerated storage. Pâtés with 28% w/w of sunflower oil were the most suitable formulation to increase the nutritional value for this kind of meat products.